Para que el periodismo sobreviva: innovar al contar las noticias y que sea rentable - Guerra Farro, Gisú Marlene (2020)
Journalist with 21 years of experience in television, covering transcendental news in Peru. Governments, their leaders, political crises, electoral campaigns, natural disasters, violent protests and demonstrations of social support were among the significant breaking news stories, that I had to report about. Most of those situations happened during the transition to live broadcasting news in the Peruvian television. The production of live news successfully reached the audience, who urgently needed to be informed from a more objective form of journalism. The media had sold their editorial contents to Alberto Fujimori’s government. Research and international broadcast coverage were also a part of my journalistic duties. I have participated in the creation of new innovative media, evolving from positions as a news producer, host and editor. With the emergence of digital revolution, journalists can take the advantage to have a new way of financing news broadcasting and opening new media on internet. The subscription can assure the financing and sustaining of new media. Important newspapers in the world have already started with success. The authentic journalism should not be afraid of new challenges.